Fruit quality of 'Tahiti' lime (Citrus latifolia Tanak) grafted on twelve different rootstocks - Stuchi, Eduardo Sanches; Martins, Antonio Baldo Geraldo [UNESP]; Lemo, Rodrigo Rodas [UNESP]; Cantuarias-Avilés, Tatiana (Sociedade Brasileira de Fruticultura, 2009)
No presente trabalho, avaliou-se a influência de doze porta-enxertos sobre a qualidade dos frutos da lima-ácida 'Tahiti' (Citrus latifolia Tanaka), clone 'IAC-5', amostrados em duas posições nas plantas, em experimento conduzido na Estação de Citricultura de Bebedouro, em um pomar de três anos. O espaçamento utilizado foi de 8.0 x 5.0m. Os porta-enxertos utilizados foram: citrangeiro 'Carrizo' (C. sinensis (L.) Osbeck x Poncirus trifoliata (L.) Raf.); os híbridos 'Cravo' x 'Swingle' (C. limonia Osbeck x P. trifoliata (L.) Raf. x C. paradisi Macf.) e 'Changsha' x 'English Small' (C. sunki Hort. ex Tan. x P. trifoliata Raf.); as tangerineiras 'Sun Chu Sha Kat' (C. reticulata Blanco) e 'Sunki' (C. sunki Hort. ex Tanaka); os limoeiros 'Cravo Limeira' e 'Cravo FCAV' (C. limonia Osbeck); o citrumeleiro 'Swingle' (P. trifoliata Raf. x C. paradisi Macf.), o tangeleiro 'Orlando' (C. reticulata Blanco x C. paradisi Macf.) e os trifoliateiros 'Rubidoux', 'FCAV' e 'Flying Dragon' (Poncirus trifoliata Raf.). Foi utilizado um delineamento em blocos casualizados, com doze tratamentos e seis repetições. Os distintos porta-enxertos induziram diferenças na qualidade dos frutos, entretanto todas as características de qualidade foram consideradas aceitáveis para a variedade, sendo bons substitutos para o limão 'Cravo'.

In the present work, the effect of twelve rootstocks on fruit quality of the nucellar clone IAC-5 of 'Tahiti' lime, (Citrus latifolia Tanaka) and the influence of fruit position on tree in fruit quality was evaluated in the Citrus Experimental Station of Bebedouro (EECB), located in the Bebedouro county, state of São Paulo, Brazil. A 8.0 x 5.0m planting frame was utilized. The evaluated rootstocks were: 'Carrizo' citrange (C. sinensis (L.) Osbeck x Poncirus trifoliata (L.) Raf.); the hybrids 'Rangpur' lime x 'Swingle' citrumello (C. limonia Osbeck x P. trifoliata Raf) and 'Changsha' x 'English Small'(C. sunki Hort. ex Tan. x P. trifoliata Raf.); the mandarins 'Sun Chu Sha Kat' (C. reticulata Blanco) and 'Sunki' (C. sunki Hort. ex Tanaka); the 'Rangpur' limes 'Cravo Limeira' and ' Cravo FCAV' (C. limonia Osbeck); the 'Swingle' citrumello (P. trifoliata Raf. x C. paradisi Macf.); the 'Orlando' tangelo (C. reticulata Blanco x C. paradisi Macf.) and the trifoliates cvs. 'Rubidoux', 'FCAV' and 'Flying Dragon' (P. trifoliata Raf.). The experiment was arranged in a randomized block design, with twelve treatments, six replicates and one plant per plot. The rootstocks induced differences in fruit quality; however, all the evaluated quality characteristics were within the values considered as normal and acceptable for the variety, constituting good alternative rootstocks for the 'Rangpur' lime. Additionally, the fruit position in the plant (northeastern or southwestern) had a significant influence on the external fruit color regardless of the rootstock.
Qualidade de frutos de limeira-ácida 'Tahiti' (Citrus latifolia Tanaka) enxertada em doze porta-enxertos
Keywords: posição do fruto; coloração do fruto; dimensões e massa dos frutos; fruit position; fruit color; fruit dimension and mass